ECONOMIC STRAIN ADAPTATION POLICY TO SOLVE CRIMES DURING THE PANDEMIC IN INDONESIA - Mohammad Faisol Soleh (Universitas Syiah Kuala, 2022)
This article examines the relationship between the national economic strain and crimes in Indonesia during the COVID-19 pandemic. This research is legal-doctrinal writing with a conceptual approach and a case approach. The data collection technique was through a literature study which was analyzed descriptively-qualitatively. The research results show; First, there is a significant relationship between the economic crisis and the high crime rate during the pandemic. The condition illustrates the strain theory, where the strain that occurs in society due to the non-fulfillment of economic needs triggers some of them to commit crimes to achieve their economic goals finally. Second, the economic strain adaptation policy can solve the crimes due to economic strain. The adaptation is to implement preventive measures by strengthening coordination and supervision between institutions providing economic stability and repressive efforts through optimizing strict law enforcement against crime during the pandemic.